Wage Inequality in its Relation with Macroeconomic Stability: A Synergetic Approach - Anna Horodecka; Liudmyla Vozna (Institute of Economic Research (IER), 2017)
The authors' researches in the field of economic equilibrium, labour market stability and working motivation; the synergetic paradigm; the research literature and statistical data dealing with wage inequality and unemployment. To present a dispersion (probabilistic) approach in using neoclassic demand and supply curves analysis and, thus, to propose a new definition of the equilibrium problem, which is closer to evolutionary paradigm; with help of the D-S curves, to prove the connection between degree of wage inequality and the general level of unemployment; to demonstrate two types of extreme macroeconomic instability in their relation with the character of wage inequality, and to regard them from the standpoint of the synergetic conception. Induction and deduction reasoning, analysis and synthesis, the method of analogy, content analysis of relevant literature, mathematical methods, interdisciplinary approach, the synthesis of orthodox (neoclassical) and heterodox (evolutionary) economics. Both situations - very low and very high wage inequality - are related with extreme macroeconomic instability. The first situation can be related not only with general poverty and homogenous, low skilled workforce, but, primarily, with absence of evolutionary change. A very high wage inequality can be related with inflexible labour markets, the relatively low level of social mobility and weak social cohesion. In the article, these two situations are compared with two types of disorder in the synergetic conception. With help of the curves of demand and supply, we demonstrate the action of macroeconomic synergistic effect, which is accompanied by economic growth, decreasing unemployment and the wage levelling. Our approach confirms that in a dynamic economy the actual level of employment is lower than potential one. Moreover, this approach can be used for diminishing the theoretical gap between such opposing interpretation of unemployment as neoclassical and Keynesian.
Keywords: B4; D63; E24; J2; J31; 330; wage inequality; unemployment; instability; evolutionary economics; synergistic effect